(untitled) (Acta Scientiarum. Health Sciences, 2016)
The search for more healthy alimentary habits has stimulated the study of new food sources. Edible mushrooms, such as the genus Agaricus, may be underscored. Current assay evaluates the dietary influence of diets supplemented with the mushroom Agaricus brasiliensis on the metabolic profile of lipids and glycemic behavior in rats. A trial with 28 male Wistar rats in 4 groups with 7 rats each was carried out during 32 days. Diets given to these groups were AIN-93 (CAS) for Group 1; AIN-93 with 1% cholesterol (CAS + COL) for Group 2; the same for Group 3 and 4, but supplemented with or without mushrooms [ (COG) and (COG + COL) respectively]. Analyses of all samples for cholesterol, triacylglycerols, hepatic cholesterol and hepatic lipids on the 32nd day showed that Agaricus mushroom modified the lipid profile, reduced total cholesterol by 16% and triacylglycerols by 26.9% and increased HDL by 60.2%, coupled to reduction of lipid and cholesterol levels in the liver and a higher elimination of lipids in the stool. Glycemic curve decreased significantly between fifteen and sixty minutes in rats fed on Agaricus supplemented diets.